New for Ukraine lichen-forming and lichenicolous fungi from Gorgany Nature Reserve - Khodosovtsev, A.Ye.; Darmostuk, V.V.; Gromakova, A.B. (Український ботанічний журнал, 2016)
Six new for Ukraine species of lichen-forming (Caloplaca borreri, Micarea viridiatra, Micarea viridileprosa,
Porina guentheri, Schismatomma cretaceum, Xylographa vitiligo) and three species of lichenicolous fungi (Didymocyrtis
pseudeverniae, Milospilum lacoizquetae, Psammina stipitata) from Gorgany Nature Reserve are reported. The materials
were collected within the area of primeval spruce forests on bark of Acer pseudoplatanus, Abies alba, Fagus sylvatica,
Pinus cembra, as well as on sandstone outcrops, wood and different lichens. The descriptions, localities, ecological and
distribution data for these species are provided. В статті наведено опис, місцезнаходження, екологічні
особливості та загальне поширення нових для України
шести видів лишайників (Caloplaca borreri, Micarea viridiatra, Micarea viridileprosa, Porina guentheri, Schismatomma
cretaceum, Xylographa vitiligo) та трьох видів ліхенофільних
грибів (Didymocyrtis pseudeverniae, Milospium lacoizquetae,
Psammina stipitata), знайдених на території природного
заповідника «Ґорґани». В статье приведены описание, местонахождения, экологические особенности и общее распространение новых
для Украины шести видов лишайников (Caloplaca borreri,
Micarea viridiatra, Micarea viridileprosa, Porina guentheri,
Schismatomma cretaceum, Xylographa vitiligo) и трех видов
лихенофильных грибов (Didymocyrtis pseudeverniae, Milospium lacoizquetae, Psammina stipitata), найденных на территории природного заповедника «Горганы».